Evaluation of an alkali-treated and hydroxyapatite-coated orthopedic implant loaded with tobramycin. (November 2019) - Janson, Oscar; Sörensen, Jan Henrik; Strømme, Maria; Engqvist, Håkan; Procter, Philip; Welch, Ken
An approximately 1-µm thick hydroxyapatite coating was biomimetically deposited on an alkali-treated, commercially available orthopedic screw surface (type II anodized titanium). Tobramycin loaded into the coating via a simple soaking method was shown to provide a sustained release above the minimal inhibitory concentration 0.2 µg/µl for up to two days. Agar diffusion tests showed that the tobramycin-loaded coating was able to produce a zone of inhibition against Staphylococcus aureus for up to five days. Biocompatibility testing using outgrowth endothelial cells and primary osteoblasts suggested that good cell compatibility of the coating can be expected in vivo. A rabbit distal femur condyle model was used for in vivo evaluation of the antibacterial efficacy of the tobramycin-loaded coating, and this pilot study showed that the release of tobramycin was sufficient to locally eliminate very large amounts of bacteria in vivo (inoculation dose 10 4 –10 5 CFU S. aureus /test site).